Analysis of Investor Reactions to The Right Issue at The IDX Before and During Covid-19 - Pathonah, Nurul (Airlangga Journal of Innovation Management, 2024)
The COVID-19 pandemic has resulted in fluctuations in movement stock prices, and greatly influenced economic conditions as well as reactions of investors regarding the rights issue policy which will influence buying and selling interest shares. The rights issue is an event where information is published as an announcement that can be used to see market reactions. This research was conducted to analyze investor reactions to the Rights Issue announcement. Using 50 samples of companies that carried out rights issues during 2017 - 2020. The inquiry about was carried out utilizing the occasion consider strategy with an advertising show approach. The ordinariness test is the Kolmogorov – Smirnov test. The statistical test used in this research is the difference between two means tests (Wilcoxon Signed Rank Test). The comes about of this inquiry appears that there's a noteworthy contrast in excess returns within the period sometime recently and after the declaration of the rights issue, be that as it may, this inquiry appears that there's no distinction in stock liquidity sometime recently and after the declaration of the rights issue. there's no distinction between the bid-ask spread sometime recently and after the declaration of the rights issue, both sometime recently and amid the widespread COVID-19 implies that the declaration of the rights issue cannot be utilized as a reference choice in an exertion to extend the liquidity of the company offers within the long-term brief, this can be since the declaration of the rights issue isn't sufficient contains data that can impact venture choices.